2023
DOI: 10.3390/nu15051141
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Probiotic Pretreatment on the Gut Microbiota and Minor Complications after Bowel Preparation for Colonoscopy: A Randomized Double-Blind, Placebo-Controlled Pilot Trial

Abstract: The aim of this study was to evaluate the effects of probiotic pretreatment on the alteration and recovery of gut microbiota after bowel preparation and its correlation with minor complications. This was a randomized, double-blind, placebo-controlled pilot trial that included participants 40–65 years of age. Participants were randomly provided probiotics (active group) or placebo (placebo group) for 1 month before the colonoscopy and their feces collected. A total of 51 participants were included in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…A total of six included studies [19,[21][22][23][26][27] in the quantitative synthesis showed numerous results in before and after-colonoscopy groups, as shown in Table 2.A and 2.B, respectively. Souza et al [23] reported a statistically significant reduction in abdominal pain symptoms in before colonoscopy probiotics groups (p=0.032).…”
Section: Final Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of six included studies [19,[21][22][23][26][27] in the quantitative synthesis showed numerous results in before and after-colonoscopy groups, as shown in Table 2.A and 2.B, respectively. Souza et al [23] reported a statistically significant reduction in abdominal pain symptoms in before colonoscopy probiotics groups (p=0.032).…”
Section: Final Resultsmentioning
confidence: 99%
“…Among the nine studies evaluated using ROB-2, eight had a low risk of bias, while one by Son et al [19] had a high risk. Concurrently, one quasi-experimental study by Bonavina et al [20] was considered as having some risk of bias concern.…”
Section: Quality Assessmentmentioning
confidence: 98%
See 3 more Smart Citations